2013
DOI: 10.15835/nbha4119015
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatic Response Variability of Quercus species in the Romanian Intensive Forest Monitoring Network

Abstract: Oaks are among the most important broad-leaved species in Romanian forests from both an economic and socio-ecological point of view. A significant decline of these species has been observed, which was first evident in various studies and investigations followed by the more results of interdisciplinary research performed in intensive monitoring plots (level II) showing that the decline is climate induced. Thus, it is important to understand the climate change conditions and factors that influence Quercus spp. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…Some of the characteristics also manifested significant correlations in July, August, and September ( Table 3). The significant positive effect of precipitation in May and June has also been proven by a number of European dendroclimatological and xylogenetic studies dealing with the sessile oak in France (Becker et al, 1994;Lebourgeois et al, 2004;Mérian et al, 2011;Michelot et al, 2012), Romania (Popa et al, 2013), Germany (Friedrichs et al, 2009), Slovakia (Petráš andMecko, 2011), Poland (Cedro, 2007;Bronisz et al, 2012), and Moravia, Czech Republic (Doležal et al, 2010). The negative effect of June (or July) temperatures has also been demonstrated repeatedly (Doležal et al, 2010;Mérian et al, 2011;Petráš and Mecko, 2011;Michelot et al, 2012).…”
Section: Discussionmentioning
confidence: 77%
“…Some of the characteristics also manifested significant correlations in July, August, and September ( Table 3). The significant positive effect of precipitation in May and June has also been proven by a number of European dendroclimatological and xylogenetic studies dealing with the sessile oak in France (Becker et al, 1994;Lebourgeois et al, 2004;Mérian et al, 2011;Michelot et al, 2012), Romania (Popa et al, 2013), Germany (Friedrichs et al, 2009), Slovakia (Petráš andMecko, 2011), Poland (Cedro, 2007;Bronisz et al, 2012), and Moravia, Czech Republic (Doležal et al, 2010). The negative effect of June (or July) temperatures has also been demonstrated repeatedly (Doležal et al, 2010;Mérian et al, 2011;Petráš and Mecko, 2011;Michelot et al, 2012).…”
Section: Discussionmentioning
confidence: 77%
“…This has been demonstrated by CZ oaks before (Doležal et al 2010), and positive response to summer precipitation has also been shown for oak chronologies from France (Mérian et al 2011), Romania (Popa et al 2013), Germany (Friedrichs et al 2009a), Slovakia (Petráš &Mecko 2011), andPoland (Bronisz et al 2012). However, responses to hydroclimate in the Czech Re public were quite weak and unstable over time.…”
Section: Discussionmentioning
confidence: 78%
“…The negative impact on forests of environmental factors was, in Romania, similar to the one described in most European countries, and there existed numerous situations in which devitalization, deterioration of vegetation state and occurrence of abnormal diebacks started to become frequent (Rossnev et al, 1994;Woo, 2009;Sonesson and Drobyshev, 2010;Popa et al, 2013;Jankowiak et al, 2014;Keca et al, 2016).…”
Section: Introductionmentioning
confidence: 55%